Orthodontic apps: an assessment of quality (using the Mobile App Rating Scale (MARS)) and behaviour change techniques (BCTs) - N. R. Siddiqui; S. J. Hodges; M. O. Sharif (SpringerOpen, 2021)
Abstract Background Apps have been shown to be an effective tool in changing patients' behaviours in orthodontics and can be used to improve their compliance with treatment. The Behaviour Change Techniques (BCTs) and quality (using MARS) within these apps have previously not been published. Objectives 1. To evaluate the quality of these apps aiming to change behaviour. 2. To assess BCTs used in patient focused orthodontic apps. Methods The UK Google Play and Apple App Stores were searched to identify all orthodontic apps and 305 apps were identified. All 305 apps were assessed for the presence of BCTs using an accepted taxonomy of BCTs (Behaviour Change Wheel (BCW)), widely utilised in healthcare. Of those containing BCTs, the quality was assessed using the Mobile App Rating Scale (MARS), a validated and multi-dimensional tool which rates apps according to 19 objective criteria. Data collection was carried out by two calibrated, independent assessors and repeated after 6 weeks for 25% of the apps by both assessors. Results BCTs were found in 31 apps, although only 18 of them were analysed for quality and 13 apps were excluded. Six different BCTs were identified: these were most commonly 'prompts/cues', and 'information about health consequences'. All apps were shown to be of moderate quality (range 3.1-3.7/5). Inter-rater and intra-rater reliability for BCT and quality assessment were excellent. Conclusions The current availability of orthodontic apps of sufficient quality to recommend to patients is very limited. There is therefore a need for high-quality orthodontic apps with appropriate BCTs to be created, which may be utilised to improve patients' compliance with treatment.